EDUKASI KESEHATAN PENTINGNYA MENGGUNAKAN MASKER SEBAGAI PENCEGAHAN PENULARAN COVID-19 MELALUI KEGIATAN POSYANDU DI DESA CIKELAT - Yusuf Iskandar; Sifa Ramadanti; Muhammad Raihan Alfauzi (LPPM Universitas Nusa Putra, 2023)
Abstract,Health conditions in Indonesia are influenced by many things. Factors that affect health in general arelifestyle, environment (social, economic, political, cultural), health services, and heredity. The percentage oftransmission is more likely in elderly individuals and those with a history of medical problems such as cardiovascular,diabetes, chronic respiratory diseases, and cancer (Kemenkes, 2020), which are more likely to develop COVID-19virus infection into a more serious disease. Our work program is educating health and how to wear masks as an effortto prevent the spread of Covid-19. The method used is to educate directly through posyandu activities in CikelatVillage, Cisolok District, Sukabumi Regency and distribute donations in the form of masks to slow down the spreadof Covid-19. This educational activity is targeted at rural communities who in fact do not understand COVID-19information.Keywords: Education, Health, Use of Masks